Development of an intergenerational wealth mobility framework for Pakistan - Areeba Khan; Sohail Saeed; Muhammad Fahad Khan; Quratul Ain (Journal of Business and Social Review in Emerging Economies, 2018)
The study is an endeavor to calculate the mobility of wealth across generations. The study is aimed to provide useful insights in the determinants of wealth linked in a manner that enables the calculation of wealth at single point in time (i.e. at the age of the eighteen and at the age of thirty).